2009
DOI: 10.1172/jci34015
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of SOX9 inhibits the growth of human and mouse melanomas and restores their sensitivity to retinoic acid

Abstract: Treatments for primary and metastatic melanomas are rarely effective. Even therapeutics such as retinoic acid (RA) that are successfully used to treat several other forms of cancer are ineffective. Recent evidence indicates that the antiproliferative effects of RA are mediated by the transcription factor SOX9 in human cancer cell lines. As we have previously shown that SOX9 is expressed in normal melanocytes, here we investigated SOX9 expression and function in human melanomas. Although SOX9 was expressed in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
107
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 27 publications
7
107
2
1
Order By: Relevance
“…During endochondral bone formation, SOX9 expression is down-regulated in growth plate chondrocytes (Leung et al 2011). The exact role of SOX9 in carcinogenesis and cancer progression is controversial because both oncogenic and tumor-suppressing functions of SOX9 have been described (Passeron et al 2009;Cai et al 2013;. Furthermore, SOX9 expression is up-regulated in several tumor types, including lung adenocarcinoma, esophageal squamous cell carcinoma and breast cancer (Müller et al 2010;Hong et al 2015;Wang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…During endochondral bone formation, SOX9 expression is down-regulated in growth plate chondrocytes (Leung et al 2011). The exact role of SOX9 in carcinogenesis and cancer progression is controversial because both oncogenic and tumor-suppressing functions of SOX9 have been described (Passeron et al 2009;Cai et al 2013;. Furthermore, SOX9 expression is up-regulated in several tumor types, including lung adenocarcinoma, esophageal squamous cell carcinoma and breast cancer (Müller et al 2010;Hong et al 2015;Wang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…SOX9 also increases apoptosis in colon tumor cells (Jay et al, 2005) and reduces cell proliferation rate, as illustrated by hyperplasia and dysplasia induced by Sox9 abrogation in the intestine epithelium (Bastide et al, 2007;Zalzali et al, 2008). The anti-proliferative activity of SOX9 was also evidenced in retinoid-treated breast cancer cell lines and melanomas (Afonja et al, 2002;Passeron et al, 2009;Muller et al, 2010). Finally, loss of SOX9 expression and promoter hypermethylation is associated with bladder cancer progression (Aleman et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…SOX9 has shown several pro-oncogenic properties, including the ability to promote proliferation, to inhibit senescence and to collaborate with other oncogenes in neoplastic transformation (Wang et al, 2008;Jiang et al, 2010;Matheu et al, 2012). But some reports demonstrated that overexpression of SOX9 in human melanoma or human endometrial carcinoma, as well as in chondrocytes, inhibited cell proliferation through P21 expression in cooperation with p53 (Panda et al, 2001;Passeron et al, 2009;Saegusa et al, 2012). Variable outcomes are likely to be correlated with the relative activation of P21.…”
Section: Discussionmentioning
confidence: 99%